Genetic analysis of artificial Triticinae amphidiploid Aurotica based on the glaucousness trait - Shpylchyn, V.V.; Antonyuk, M.Z.; Ternovska, T.K. (Цитология и генетика, 2014)
Changes in plant genomes of hybrid origin which become apparent on different levels of phenotypic manifestation of genetic and epigenetic changes are an important object of cytogenetics and molecular genetics. The changes in expression of the glaucousness trait in the artificial Triticinae amphidiploid Aurotica (AABBTT) were investigated; haplotypes of plants with the appearance of glaucous and non-glaucous genes were determined by hybridization experiments. It was suppoted that the changes in expression can be explained by (epi)mutations abolishing the efficiency of dominant alleles of orthologous series of glaucous inhibitor gene Iw. Analysis of F2 population with SSR markers specific to 2B and 2D wheat chromosomes and 2T chromosome of Aegilops mutica manifested associated inheritance of the Wms 102 and Wms 702 loci, which mapped to the short arm of chromosome 2D. The Wms 702 marker was linked to the Iw2(T) gene and can now be used to detect that gene. Изменения в геноме растений гибридного проис-хождения, которые проявляются на разных фенотипических уровнях реализации генетических и эпигенетических изменений, интенсивно исследуются цитогенетикой и молекулярной генетикой. Изучали изменения экспрессии признака наличие/отсутствие воскового налета у искусственного амфидиплоида Авротика (Triticinae, AABBTT). Гибридологическим анализом установлены гаплотипы растений с контрастными фенотипами и показано, что изменение экспрессии признака связано с (эпи)мутацией, которая приводит к утрате активности доминантного аллеля ортологической серии генов Iw —ингибиторов воскового налета у пшеницевых. Микросателлитный анализ расщепляющихся популяций по SSR-локусам, специфичным для 2B и 2D хромосом пшеницы и 2T хромосомы эгилопса, показал сцепленное наследование локусов Wms 102 и Wms 702, локализованных на плече 2DS, а локус Wms 702 сцеплен с геном Iw2(T) и может быть использован для определения этого гена. Зміни у геномі рослин гібридного походження, які виявляються на різних фенотипних рівнях реалізації генетичних та епігенетичних змін, інтенсивно досліджуються цитогенетикою та молекулярною генетикою. Вивчали зміни експресії ознаки наявність/відсутність воскової осуги у штучного амфідиплоїда Авротика (Triticinae, AABBTT). Гібридологічним аналізом встановлено гаплотипи рослин з контрастними фенотипами та показано, що зміна експресії ознаки пов’язана з (епі)мутацією, яка призводить до втрати активності домінантного алеля ортологічної серії генів Iw — інгібіторів воскової осуги у пшеницевих. Мікросателітний аналіз популяций, що розщеплюються, за SSR-локусами, специфічними для 2B та 2D хромосом пшениці та 2T хромосоми егілопсу, показав зчеплене успадкування локусів Wms 102 та Wms 702, локалізованих на плечі 2DS, а локус Wms 702 зчеплений з геном Iw2(T) та може бути використаний для визначення цього гена.